(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يحاول هذا البحث قراءة النص الدرّاجي لرصد تجربة الغربة والحنين فيه، إذ عكست قصيدة الغربة والحنين رؤية الشاعر للمكان والزّمان. وقد أسهم المكان والزّمان في تنمية دلالة الغربة والحنين وصنع خصوصية التجربة كون تجربة الشاعر ابن درّاج في الغربة والحنين هي تجربة في مواجهة المكان والزّمان، فقد كان مكان الغربة منطلقاً لممارسة الحلم المتواصل الذي يؤكد العلاقة الحميمة التي تربط الشاعر بمكان الألفة. أمّا إحساس ابن درّاج بقوة التغيير التي مارسها عليه الزّمان جعل نفسه تغترب عن الزّمان الحاضر (الشيخوخة)، وتحنّ إلى الزّمان الماضي ( الشباب). This research aims to study The Darraji Poem, to monitor the experience of exile and nostalgia in it, as the poem reflected the alienation and longing to see the poet of place and time. The shares of space and time in the development of a sign of alienation and longing and making the privacy of the experiment the fact that the experience of the poet Ibn Darrag in exile, and nostalgia is the experience in the face of time and place; was a place of exile starting point for the exercise of the dream continued, which emphasizes the close relationship that binds the poet place of familiarity. Ibn Darrag sense strongly change exerted by the time he made himself ngterb for the present time ( old- aging ), and yearns for the past decade ( the youth ).